Employers Unions: Potential in Social Partnership - Лариса Евгеньевна Петрова (Journal of Economic Sociology, 2010)
The paper analyses the characteristics of federal and regional unions of employers and their relations with trade unions in the practice of social partnership. The relations between three partners are in the focus. They are employers, trade unions and the state.